Multi-Virulence-Locus Sequence Typing Identifies Single Nucleotide Polymorphisms Which Differentiate Epidemic Clones and Outbreak Strains of Listeria monocytogenes - Chen, Yi (American Society for Microbiology, 2007)
A recently developed multi-virulence-locus sequence typing (MVLST) method showed improved discriminatory power for subtyping genetically diverse Listeria monocytogenes isolates and identified epidemic clone II isolates associated with two recent U.S. multistate listeriosis outbreaks. To evaluate the ability of MVLST to distinguish other epidemic clones and outbreak strains of L. monocytogenes, 58 outbreak-related isolates from 14 outbreaks and 49 unrelated isolates were analyzed. Results showed that MVLST provided very high discriminatory power (0.99), epidemiological concordance (1.0), stability, and typeability. MVLST accurately identified three previously known epidemic clones (epidemic clones I, II, and III) and redefined another epidemic clone (epidemic clone IV) in serotype 4b of L. monocytogenes. A set of 28 single nucleotide polymorphisms (SNPs) differentiated all epidemiologically unrelated isolates. A subset of 16 SNPs differentiated all epidemic clones and outbreak strains. Phylogenetic analysis showed congruence between MVLST clusters, serotypes, and previously defined genetic lineages of L. monocytogenes. SNPs in virulence genes appear to be excellent molecular markers for the epidemiological investigation of epidemics and outbreaks caused by L. monocytogenes.